2021
DOI: 10.1016/j.bbih.2021.100343
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise increases immune responses to SARS CoV-2 in a previously infected man

Abstract: Evidence is emerging that exercise and physical activity provides protection against severe COVID-19 disease in patients infected with SARS-CoV-2, but it is not known how exercise affects immune responses to the virus. A healthy man completed a graded cycling ergometer test prior to and after SARS-CoV-2 infection, then again after receiving an adenovirus vector-based COVID-19 vaccine. Using whole blood SARS-CoV-2 peptide stimulation assays, IFN-γ ELISPOT assays, flow cytometry, ex vivo v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…During Visit 3 , the resting serum sample was also used to confirm whether all vaccinated individuals had seroconverted and presented with a positive SARS-CoV-2 IgG titer. To exclude the possibility of including participants who had been infected naturally between laboratory visits, whole blood samples collected in two lithium heparin coated tubes were stimulated with overlapping peptide pools spanning the breadth of the spike, membrane, and nucleocapsid antigens (10 μg/mL; Miltenyi) before measuring IFN-γ in plasma by ELISA (R&D Systems; Minneapolis, MN) following methods we recently described ( 16 ). No responses to membrane or nucleocapsid antigen were found post vaccine in the participants who had not been infected naturally (data not shown)( 17 ).…”
Section: Experimental Designmentioning
confidence: 99%
“…During Visit 3 , the resting serum sample was also used to confirm whether all vaccinated individuals had seroconverted and presented with a positive SARS-CoV-2 IgG titer. To exclude the possibility of including participants who had been infected naturally between laboratory visits, whole blood samples collected in two lithium heparin coated tubes were stimulated with overlapping peptide pools spanning the breadth of the spike, membrane, and nucleocapsid antigens (10 μg/mL; Miltenyi) before measuring IFN-γ in plasma by ELISA (R&D Systems; Minneapolis, MN) following methods we recently described ( 16 ). No responses to membrane or nucleocapsid antigen were found post vaccine in the participants who had not been infected naturally (data not shown)( 17 ).…”
Section: Experimental Designmentioning
confidence: 99%
“…The underlying systemic inflammation contributes to muscle atrophy indirectly (lung obstruction and forced inactivity) or directly (increased muscle wasting, necrosis, fibrosis and autophagy, and mitochondrial dysfunction), while viral antigen mimicry might cause muscle denervation in peripheral nerves. While physical activity (PA) has been identified as a predictive and protective factor against severe forms of COVID-19 [ 17 , 18 , 19 , 20 ], it has also been suggested as a key factor for rehabilitation [ 21 , 22 , 23 ], both for the acute and long-term consequences of this new global disease. According to a survey questioning the specific rehabilitation needs reported by post-COVID-19 patients themselves [ 24 ], exercise guidance appears to be a primary concern.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study on a healthy man, Baker et al ( 46 ) concluded that acute exercises like incremental continuous cycling affect multiple SARS-CoV-2 specific T-cell mobilization to the blood vessels and elevation of neutralizing antibodies temporarily, which can be caused by increased lymphatic flow due to exercise. Furthermore, exercise increased the IFN- response to SARS-CoV-2 peptide stimulation in the blood.…”
Section: Discussionmentioning
confidence: 99%